Critical Evaluation of the Use of Technology in Education (Docentes 2.0 Journal, 2025)
Nowadays, due to technological advances, the educational system has been forced to make significant changes to its curricular grids to adapt to these new challenges. However, integrating technology in the classroom involves facing various myths that have been debated in educational organizations. The main objective of the research was to demonstrate that some of these myths are unfounded and, at the same time, to facilitate an analytical evaluation of the use of technology in educational environments. The study is framed within the humanistic paradigm, a systematic method with a qualitative approach, a documentary-type narrative design, and a cross-sectional section. A literature review was carried out that included studies from databases specialized in education and technology, considering 17 investigations published between 2010 and 2023. The techniques used were bibliographic review and analysis of the texts selected for the study. The research results show that technologies can contribute to personalizing learning and serve as motivational tools, although their impact depends on the context in which they are implemented. The discussion highlights the importance of thoughtful and evidence-based use, avoiding creating unrealistic expectations about its effectiveness. Finally, considering its advantages and limitations, it is concluded that a balanced approach is needed in integrating technology into the educational system.
Keywords: Technological impact; evidence-based assessment; use of technology; education